EFFECT OF OBSTRUCTIVE SLEEP APNEA (OSA) RISK LEVELS ON BOSTON NAMING TEST SCORES TO THE POPULATION IN MATARAM - Sulistyaningrum, Dwi; Lestari, Rina; Harahap, Herpan Syafii (MNJ (Malang Neurology Journal), 2021)
Background: Obstructive Sleep Apnea (OSA) is one of the most common respiratory disorders found in society. This condition is often found in men with obesity, men with hypertension history, and elderly. In relation to this, it is found that the researches on the effect of OSA risk level on language functions is rarely done. Therefore, this study is aimed at investigating the effect of OSA risk levels on Boston Naming Test score to the population in Mataram. Objective: to investigate the effect of OSA risk levels on language functions used the Boston Naming Test to the population in Mataram.Methods: This study belongs to analytic descriptive study with cross sectionalÂ  approach. Held in Udayana Park, Dasan Sari, Mataram in May 2017 and September 2018. This study involved 132 respondents by ages among 40-74 years old. They are Chosen based on inclusion criteria. The OSA risk level was measured using The STOP-Bang questionnaire while language functions was measured using the Boston Naming Test. After That, the Mann-whitney comparative test was employed to analyzed the data.Results: The result of this study showed that, from 132 respondents, it was found that there were 66 (50%) respondents had a high risk level of OSA, and 82 (62%) respondents had language function disorders. Besides, the Mann-Whitney comparative analysis showed no effect on the risk level of OSA on Boston Naming Test score (p > 0.05).Conclusion: The risk level of OSA has no effect on Boston Naming Test score to the population aged 40-74 years in Mataram.